TOWARDS AN INCLUSIVE ISLAMIC PARADIGM: RECONSTRUCTION OF DISABILITY IN RELIGIOUS TRADITIONS - Barkatullah Amin; Ani Cahyadi; M. Noor Fuady; Aulia Azmina Fajriati (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2026)
AbstractThis article aims to analyze the Islamic paradigm on disability and offer a reconstruction of a more inclusive, humanistic, and just religious understanding. This study uses library research with a conceptual-critical approach through an analysis of contemporary Islamic literature, disability studies, and socio-religious ethics. The results show that Islam has a strong ethical foundation through the concepts of karāmah al-insān, al-'adl, sunnatullāh, and maqāṣid al-sharī'ah, which place all humans in equal dignity. However, the stigma against people with disabilities is still reproduced through biased religious interpretations, religious ableism, and social constructions that make normality the primary measure of human worth. This study finds that disability should not be understood as a deviation from nature, but rather as part of the diversity of human abilities (human diversity). Furthermore, exclusion of people with disabilities stems more from social, cultural, and institutional barriers than from Islamic teachings themselves. Based on these findings, this article proposes a reconstruction of the Islamic paradigm on disability through a shift from a deficit approach to a human diversity paradigm, a reinterpretation of religion oriented toward justice and participation, and a strengthening of the maqāṣid al-sharī'ah as an ethical framework for developing more inclusive religious spaces, Islamic education, and digital environments. These findings affirm that disability inclusion is a manifestation of fundamental Islamic values of human dignity, social justice, and mercy for all humanity.Keywords: Disability, inclusive Islam, human diversity, maqāṣid al-sharī'ah, religious ableism.AbstrakArtikel ini bertujuan menganalisis paradigma Islam tentang disabilitas serta menawarkan rekonstruksi pemahaman keagamaan yang lebih inklusif, humanis, dan berkeadilan. Penelitian ini menggunakan metode kepustakaan (library research) dengan pendekatan konseptual-kritis melalui analisis literatur keislaman kontemporer, disability studies, dan etika sosial-keagamaan. Hasil penelitian menunjukkan bahwa Islam memiliki fondasi etik yang kuat melalui konsep karāmah al-insān, al-'adl, sunnatullāh, dan maqāṣid al-sharī'ah yang menempatkan seluruh manusia dalam martabat yang setara. Namun, stigma terhadap penyandang disabilitas masih direproduksi melalui bias tafsir keagamaan, religious ableism, serta konstruksi sosial yang menjadikan normalitas sebagai ukuran utama keberhargaan manusia. Kajian ini menemukan bahwa disabilitas tidak sepatutnya dipahami sebagai penyimpangan dari fitrah, melainkan sebagai bagian dari keberagaman kemampuan manusia (human diversity). Selain itu, eksklusi terhadap penyandang disabilitas lebih banyak bersumber dari hambatan sosial, budaya, dan kelembagaan daripada dari ajaran Islam itu sendiri. Berdasarkan temuan tersebut, artikel ini menawarkan rekonstruksi paradigma Islam tentang disabilitas melalui pergeseran dari pendekatan defisit menuju paradigma human diversity, reinterpretasi keagamaan yang berorientasi pada keadilan dan partisipasi, serta penguatan maqāṣid al-sharī'ah sebagai kerangka etik bagi pengembangan ruang keagamaan, pendidikan Islam, dan lingkungan digital yang lebih inklusif. Temuan ini menegaskan bahwa inklusi disabilitas merupakan manifestasi nilai-nilai fundamental Islam tentang kemuliaan manusia, keadilan sosial, dan rahmat bagi seluruh manusia.Kata Kunci: Disabilitas, Islam inklusif, human diversity, maqāṣid al-sharī'ah, religious ableism.